NEIL3 and TOP2A as key drivers of esophageal cancer through WNT signaling - Hui Li; Panpan Wang; Huijuan Chen; Yanyan Shao; Hui Luo (Biomolecules & Biomedicine)
Esophageal cancer (EC) is a highly aggressive malignancy with limited treatment options. Nei like DNA glycosylase 3 (NEIL3) and DNA topoisomerase II alpha (TOP2A) have been identified as potential therapeutic targets, though their roles in EC remain unclear. This study investigates the effects of NEIL3 overexpression and TOP2A knockdown, focusing on the WNT signaling pathway. ECA109 esophageal cancer cells were used to assess the impact of NEIL3 overexpression and TOP2A knockdown on proliferation, colony formation, migration, invasion, and apoptosis. The involvement of the WNT signaling pathway was also explored. NEIL3 overexpression significantly enhanced proliferation, colony formation, migration, and invasion while reducing apoptosis. In contrast, TOP2A knockdown suppressed these functions and promoted apoptosis, independent of NEIL3. NEIL3 overexpression could not reverse the effects of TOP2A knockdown. Both NEIL3 and TOP2A acted through the WNT signaling pathway. In vivo, NEIL3 knockdown reduced tumor size and weight via WNT pathway modulation. NEIL3 and TOP2A play key roles in EC progression through the WNT signaling pathway. Targeting these molecules may offer promising therapeutic strategies for EC.